Effect of Reflective Objects of Different Colors to the Output Voltage-Distance Characteristics of Sharp GP2D120 IR Sensor - Mohd Rusdy , Yaacob; Nik Anwar, Nik Syahrim (2011)
This paper presents a study on the effect of reflective objects with different colors to the output voltage-distance characteristics of Sharp GP2D120 IR Sensor, which operates by employing the principle of single point triangulation. The study was conducted by using plastic materials with four different colors, in which the distance for each of them was measured by a Sharp GP2D120 IR Sensor mounted on a constructed experimental setup. The results obtained shows the output-voltage-distance characteristics which indicates that; a white color object is having the highest level of reflectivity, followed by gray, transparent and black color objects.